Does Innovative Work Behavior Matter for Performance? Green Talent Management and Green Servant Leadership in the Healthcare Industry - Rima Rahmayanti; Muafi - Muafi; Ahmad Johan (Universitas Muhammadiyah Yogyakarta, 2024)
This study aims to analyze the influence of green talent management and green servant leadership on employee performance while also considering the mediating role of innovative work behavior and the moderating role of green servant leadership in the relationship between green talent management and innovative work behavior. It was carried out in the context of employees in the health industry in Bandung. This study utilized a quantitative approach with a causal explanation to test the hypotheses. The respondents were employees who worked in private hospitals in Bandung, with 190 sample sizes selected using purposive sampling. The data were collected and processed using structural equation modeling with the help of Smart PLS software. The results revealed that green talent management and green servant leadership influenced employees’ innovative work behavior, leading to job performance. Moreover, green servant leadership could also strengthen the influence of green talent management on innovative work behavior. This study contributes to the understanding of the concept of environmentally-friendly business through innovative work behavior so it can improve work performance by adopting green practices, thereby reducing the damage caused by the organization. Furthermore, organizations must also consider that environmentally-friendly business practices are a concern and that a strong sensitivity must be instilled.